Annular pancreas with choledocholithiasis in an adult male patient: a case report - Milev, Ilija; Karagjozov, Panche; Mitevski, Aleksandar; Mihailov, Marjan (International Surgery Journal, 2019)
Annular pancreas is very rarely presented with a clinical picture of obstructive jaundice, usually due to some biliopancreatic malignancy rather than choledocholithiasis which make our case unique. We are presenting a 60-year-old male patient with a 6 mounts old medical history of right upper quadrant pain and intermittent jaundice. On ultrasonography a common bile duct stone was detected with dilatation of the biliary tree and gallstones with edematous wall of the gallbladder. On gastroscopy narrowing of the duodenum was registered. On ERCP the papilla Vateri could not be cannulated and there was a substantial amount of retained food in the duodenal bulb and antral part of the stomach. MRCP showed extensive dilatation of the whole biliary tree from several stones in the distal part of the common bile duct. At the operation there was a ring of pancreatic tissue about 2 cm wide that surrounded the second portion of the duodenum. The operation proceeded with choledochotomy, choledocholythotomy, L-L choledocho-duodenostomy and partial resection of the pancreatic ring. After three mounts the patient had gain weight, had no pain or any other symptoms and control gastroscopy showed normal finding.